Factors Related to the Retention of Contract Employee Health Workers at Ulunambo Public Health Centre, Morowali Regency - Napirah, Muhammad Ryman; Rahman, Nurdin; Laida, Marsia; Sulaiman, Miftahul Haerati; Laba, Stefiani Bengan (Media Publikasi Cendekia Indonesia, 2023)
The retention of health workers at the public health center is influenced by various factors, including work design, employee relations, career opportunities, and leadership. The decline in the number of contract employee health workers at Ulunambo Public Health Centre is evident from the data on the number of health workers. In 2014, there were 2 people; in 2015, there were 2 people; in 2016, there was 1 person, and in 2017, it dropped to 2 people. The purpose of this research is to investigate the relationship between work design, employee relations, career opportunities, and perceptions of leadership with the retention of health workers at Ulunambo Public Health Centre, Morowali Regency. The research employed an analytical survey approach with a cross-sectional study design. The sample size consisted of 33 respondents. Data were analyzed using univariate and bivariate methods at a confidence level of 95% (p < 0.05). The results of the chi-square test indicate a significant relationship between work design, employee relations, career opportunities, perceptions of leadership, and the retention of health workers (p < 0.05). It is recommended that Ulunambo Public Health Centre regularly provides training, information, and opportunities for employees seeking career development. Additionally, improving communication between management and employees through regular interactions is crucial. Furthermore, conducting regular supervision of employees' work performance is also advised.